2006
DOI: 10.1210/jc.2005-2793
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fibroblast Growth Factor Receptor 1 Mutations in Patients with Congenital Hypogonadotropic Hypogonadism with and without Anosmia

Abstract: We identified novel mutations in KAL1 and FGFR1 genes in IHH patients. FGFR1 mutations were identified in 17% of the patients with olfactory abnormalities and in one of 34 normosmic IHH patients. In addition, isolated anosmia was identified in two unrelated females as a partial phenotypic manifestation of FGFR1 defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 34 publications
7
76
1
7
Order By: Relevance
“…Our study of 50 patients with IHH identified six novel heterozygous FGFR1 mutations, including a mutation in the alternatively spliced exon 8A of this gene. The frequency of FGFR1 mutations in KS and in normosmic IHH probands was 14% (3 in 21) and 10% (3 in 29), respectively, which is consistent with results presented in other studies (6,13,14,(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study of 50 patients with IHH identified six novel heterozygous FGFR1 mutations, including a mutation in the alternatively spliced exon 8A of this gene. The frequency of FGFR1 mutations in KS and in normosmic IHH probands was 14% (3 in 21) and 10% (3 in 29), respectively, which is consistent with results presented in other studies (6,13,14,(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, our study provides additional evidence for a role of the FGFR1-IIIb isoform in the pathogenesis of IHH, and indicates the need to include routine sequencing of exon 8A (in addition to exon 8B) in genetic screening of both KS and normosmic IHH in populations of all ethnicities. This is important because researchers occasionally exclude exon 8A from their genetic analysis (23,33), leading to the risk of missed mutations. It remains to be clarified whether the relative rarity of observed exon 8A mutations is due to lack of appropriate screening of this exon in the DNA sequence analysis, to the absence of phenotypic expression of most mutations in this exon, or to a severe effect of most mutations in this exon that would be incompatible with life.…”
Section: Discussionmentioning
confidence: 99%
“…Since that observation, several FGFR1 mutations, all of which occurred in the FGFR1IIIc isoform and spanned all of the functional domains of the receptor, have been identified in KS-affected individuals and in patients with nICH. 26,27 Similar to KAL1 defects, other nonreproductive and non-olfactory disorders, such as cleft palate or lip, dental agenesis and bimanual synkinesis, are associated with KS due to FGFR1 defects. 15 An important phenotypic variability has been reported in mutated FGFR1 in unrelated probands and mixed pedigrees.…”
Section: Fgfr1 and Fgf8mentioning
confidence: 99%
“…7,11 -13,65,73 Lastly, bimanual synkinesis is highly prevalent in KAL1 (maybe 475% of the cases), 17,22 but seems to be much less common in KAL2. 7,12 10 which could be related to the known function of prokineticin-2 signalling in behavioural circadian rhythms, including sleep -wake and ingestive behaviour. 74 The prevalence of sleeping and eating disorders in KS patients, however, remains to be determined.…”
Section: Genotype -Phenotype Correlationmentioning
confidence: 99%